RETINOPATI DIABETIK: PATOGENESIS, DIAGNOSIS, TATALAKSANA KINI DAN MASA DEPAN - Ulfayani, Nabila; Haitsam, Muhamad (RSUD Dr. Saiful Anwar Province of East Java, 2023)
Diabetic Retinopathy (RD) is the main cause of blindness in people of productive age worldwide. Poor control of hyperglycemia and blood pressure are essential risk factors for the development of RD. This condition will trigger the occurrence of biomolecular mechanisms that cause damage to vessels and cells in the retina and develop into RD. The early stages of RD are generally asymptomatic, so it is recommended to perform RD screening as soon as the patient is diagnosed with type 2 DM and every 5 years for type 1 DM patients. RD therapy can be carried out with a non-pharmacological and pharmacological approach that is applied based on the level of severity to minimize the progression of RD. Apart from conventional therapy, there are potential therapies in the future, which include oral pharmacological therapy, genetic therapy, stem cell therapy, and CRISPR-Cas-Based therapy.